Phosphorus Fertilizer Recommendations for Sugarcane Production on Florida Organic Soils - J. Mabry McCray; Ronald W. Rice; Alan L. Wright (EDIS)
Much of the sugarcane grown in South Florida is on organic soils in the Everglades Agricultural Area, which is a phosphorus-limited system. Phosphorus loads in drainage water in the Everglades Agricultural Area are an environmental concern, so it is important for sugarcane growers to use best management practices such as soil testing and to follow fertilizer recommendations. This document contains updated UF/IFAS phosphorus fertilizer recommendations for Florida organic soils. This 7-page fact sheet was written by J. Mabry McCray, Ronald W. Rice, and Alan L. Wright, and published by the UF Department of Agronomy, July 2012.